THE EFFECT OF HEALTH EDUCATION ABOUT DISMENORE ON CHANGES TO DISMENORE PAIN LEVEL IN ADOLESCENT CLASSES IN SMAN 4 BOGOR CITY IN 2018: PENGARUH PENDIDIKAN KESEHATAN TENTANG DISMENORE TERHADAP PERUBAHAN TINGKAT NYERI DISMENORE PADA REMAJA KELASXII DI SMAN 4 KOTA BOGOR TAHUN 2018 - Magdalena Agu Yosali; Marina Yuniyanti (Jurnal Ilmiah Wijaya, 2018)
The background: Dysmenorrhea is the painfulmenstrual period around abdomen. It is called the primary dysmenorrhea if there is no primary cause found. Dysmenorrhea can be a pain in the lower part of stomach which the feeling is like a prick in your stomach. In Indonesia the number incident of primary dysmenorrhea In the amount of 54,89% while the rest are the secondary type. Dysmenorrhea effect can cause 14% of teenage patients cannot attend in the class and do the dailyactivities.The aim: This research purpose is to prove the influence of educational health toward dysmenorrhea, regarding to the alteration of painful level of dysmenorrhea, over the teenagers grade XII at 4 senior high school Bogor city.The methods: The type of the study is the experimental research study with Non Equivalent Control Group method. The technic of collecting the sample is by using the theory of quota sampling with amount of 66 students. The sample is divided into two groups,the intervention and the control group, which the total of each group is 33 persons. The collecting data method of this research is through questioner.The result: The result of the research using non-parametric test Mann-Whitney is to show the number of p-value, 0,001. And because of p-value 0,001 < α (0,05), subsequently Ho is declined which means there is the influence of educational health toward dysmenorrhea, concerning to the alteration of painful level of dysmenorrhea.The conclusion: There is an influence of educational health toward dysmenorrhea, concerning to the alteration of painful level of dysmenorrhea itself.The suggestion: We expect soon this counseling about reproduction health in every school more enhanced in time to time,in particular about the educational health of dysmenorrhea, in case the teenager especially the girls who had experiences in dysmenorrhea know how to manage the pain as well.